Topical Application of Chinese Formula Yeliangen Promotes Wound Healing in Streptozotocin-Induced Diabetic Rats - Abdulbaset Al-Romaima; Xiong Guan; Xihui Qin; Yinan Liao; Guiming Qin; Shixiong Tang; Jie Feng (Journal of Diabetes Research)
Diabetic wound is one of the most severe complications of diabetes mellitus (DM). Despite the associated risks of wound healing impairment in diabetes, treatment strategies remain limited. Yeliangen (YLG) is a Chinese formulation mainly composed of the rhizome of Coptis chinensis, the root of Isatis tinctoria, and the leaf of Isatis indigotica. We investigated the wound healing effects of YLG in type 2 diabetic (T2DM) rats, which were induced by intraperitoneal administration of streptozotocin after a high-fat diet for four weeks. 3×3 cm2 full-thickness excisional wounds were created on the dorsal surface of rats and then divided to control (DC), negative (DPJ), positive (DPC), and YLG-treated (DYLG) groups. Rat’s wounds were treated twice daily for 21 days. Wound area and wound contraction were detected on days 0, 3, 7, 14, and 21. Histopathological examinations were performed by H&E staining and immunohistochemistry (IHC). The biochemical parameters, mRNAs, and protein expressions were analyzed through enzyme-linked immunoassays (ELISA), qPCR, and western blot, respectively. Compared with other groups, the histological changes of wound tissue in the DYLG group were improved, and the expressions of CD31, eNOS, and PCNA were significantly upregulated. Besides, YLG significantly reduced the inflammatory factors’ expressions of TNF-α, NF-κB, MMP-9, and IL-1B on days 7, 14, and 21 postwounding. Moreover, YLG induced angiogenesis and neovascularization by significantly increasing the levels of VEGF, TGF-β1, EGF, PDGF, and SDF-1α on days 3, 7, and 14. In conclusion, YLG improved wound healing by reducing inflammation and increasing angiogenesis which may provide an alternative and effective approach for diabetic wound therapy.